2020
DOI: 10.1186/s12937-020-00597-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern and nutrient intakes in association with non-communicable disease risk factors among Filipino adults: a cross-sectional study

Abstract: Background: This study evaluated the relationship between dietary quality and food patterns of Filipino adults and the rising prevalence of selected cardiometabolic non-communicable disease (NCD) risk factors. Methods: This is a cross-sectional study that examined the association of dietary pattern and NCDs using data collected in the 2013 National Nutrition Survey. A total of 19,914 adults aged 20 years and above were included in the analyses. The Alternative Healthy Eating Index (AHEI-2010) was used to chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…It has been reported that cereals, mainly white rice, constitute half of the daily food intake of Filipino adults and the vegetable protein intake is inadequate [ 36 ]. Another study also demonstrated that a low intake of vegetables, fruits, and dairy is common because of the rice-dominant diet with few nutrient-dense foods in the Philippines [ 37 , 38 , 39 ]. The results of this study showed that animal protein intake during pregnancy was inadequate, and that vegetable protein intake was very inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cereals, mainly white rice, constitute half of the daily food intake of Filipino adults and the vegetable protein intake is inadequate [ 36 ]. Another study also demonstrated that a low intake of vegetables, fruits, and dairy is common because of the rice-dominant diet with few nutrient-dense foods in the Philippines [ 37 , 38 , 39 ]. The results of this study showed that animal protein intake during pregnancy was inadequate, and that vegetable protein intake was very inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…The factors extracted were rotated using varimax rotation to achieve a simpler structure [35]. Food groups with factor loading values of ≥|0.25| were regarded as significantly contributing to a pattern [6,36]. A six-factor solution was finally selected considering to the aforementioned empirical criteria in conjunction with the substantive meaning of the factor loadings.…”
Section: Dietary Pattern Analysismentioning
confidence: 99%
“…However, the literature mostly focuses on diet-disease relationships. To the best of our knowledge, only one study on food patterns and noncommunicable disease risk factors was implemented in the Philippines [6]. Therefore, it is critical to advance research on dietary patterns to improve nutrition programs in low and middle-income countries as well as in specific vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing patients with a deficiency in micronutrients to those who do not have a deficiency, patients with a deficiency had at least double the CV events; thus, micronutrients from FV are essential to heart health and CVD. Additionally, various studies showed a strong correlation between the Mediterranean diet which contains lots of FV and <7 glasses of fruit wine per a week on reducing CVD and total all-cause mortality [33,56,57,[60][61][62].…”
Section: Serious Cardiovascular or Cerebrovascular Diseasesmentioning
confidence: 99%
“…Nevertheless, the WHO recommends a daily intake of 400 g (a minimum of 5 servings) of FV to aid with weight-loss and reduce the risk of obesity. Moreover, the most recommended healthful diet is one that is particularly rich in a variety of FV [61,62,70,75,76,78,79,81,83,84].…”
Section: Obesitymentioning
confidence: 99%